2018
DOI: 10.1016/j.ttbdis.2018.06.006
|View full text |Cite
|
Sign up to set email alerts
|

The oligopeptide ABC transporter OppA4 negatively regulates the virulence factor OspC production of the Lyme disease pathogen

Abstract: Borrelia burgdorferi sensu lato, the agent of Lyme disease, exists in nature through a complex enzootic life cycle that involves both ticks and mammals. The B. burgdorferi genome encodes five Oligopeptide ABC transporters (Opp) that are predicted to be involve in transport of various nutrients. Previously, it was reported that OppA5 is important for the optimal production of OspC, a major virulence factor of B. burgdorferi. In this study, possible role of another Oligopeptide ABC transporter, OppA4 in ospC exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 59 publications
1
4
0
Order By: Relevance
“…Zhou et al . [ 42 ] recently noted that expression of OspC is dysregulated in an oppA4 mutant; therefore, we confirmed that our mutants temperature-shifts normally ( S1C Fig ). For complementation, we inserted the oppA1 or oppA2 coding regions into cp26, each preceded by the 500 bp upstream of oppA1 , which contains the native operonic promoter ( Fig 1A ) [ 17 ].…”
Section: Resultssupporting
confidence: 89%
“…Zhou et al . [ 42 ] recently noted that expression of OspC is dysregulated in an oppA4 mutant; therefore, we confirmed that our mutants temperature-shifts normally ( S1C Fig ). For complementation, we inserted the oppA1 or oppA2 coding regions into cp26, each preceded by the 500 bp upstream of oppA1 , which contains the native operonic promoter ( Fig 1A ) [ 17 ].…”
Section: Resultssupporting
confidence: 89%
“…However, both Rel bbu and DksA contribute to the expression of ABC-type oligopeptide transporter genes [ 11 , 25 ]. Oligopeptide transporters have also been linked to expression of virulence genes like OspC [ 81 , 82 ]. However, the interplay between the pH environment, ATP levels, oligopeptide transporters, DksA and (p)ppGpp requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of bosR is also induced during nutrient stress in a Rel Bbu , responsible for the synthesis and hydrolysis of (p)ppGpp, dependent manner 65 . BadR, OppA4, and CsrA have proposed roles in bosR transcriptional regulation 64 , 66 – 68 . BadR and OppA4 repress bosR expression and the presence of CsrA is responsible for an increase in bosR transcription.…”
Section: Discussionmentioning
confidence: 99%